The Legal Nature of Exception of Contract Non-Performance In The French Civil Code "Comparative Legal Study: Comparative Study - حورية لشهب; سالم زينب (Journal of Legal Sciences, 2019)
The exception of contract non-Performance represents an important mechanism in the implementation of obligations. It enables a contractor to refrain from implementing its obligation until the other party has fulfilled its obligations. It is a means of defense, pressure and guarantee of its rights. It is stipulated in articles 161 of the Egyptian Civil Code and Article 123 of the Civil Code While it was not provided for in the French Civil Code except after the issuance of Order No. 2016-131 on the reform of the system of contracts and public order and the establishment of obligations in articles 1217, 1219 and 1220 thereof. These texts, although they did not show the basis on which the exception of contract non-Performance, leaving this task to jurisprudence, it showed the legal nature that distinguishes him from other mechanisms similar to him, such as the right to imprisonment, dismissal and set-off.